2018
DOI: 10.3389/fphys.2018.01833
|View full text |Cite
|
Sign up to set email alerts
|

A Phylogenomic Framework and Divergence History of Cephalochordata Amphioxus

Abstract: Amphioxus, or cephalochordates, are often used as the living invertebrate proxy of vertebrate ancestors and are widely used as evolutionary biology models of chordates. However, their phylogeny, divergence history, and speciation characteristics remain poorly understood, and phylogenomic studies to explore these problems lacking entirely from the literature. Here, we determined a new transcriptome of Branchiostoma japonicum. Combined with mass sequences of all other 18 species, a 19-way phylogeny was construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…When we used the high-depth sequencing data (43.3X) to identify variations in Branchiostoma, the polymorphism rate increased to 3.69% ( Table 1, Table S1), which is still smaller than that of previously published reports (4% for B. floridae and 5.37% for B. belcheri) [2,3]. e difference in the polymorphism rate between B. floridae and B. belcheri is likely because both species have undergone a long period of independent evolution since they diverged from the most recent common ancestor approximately 100 million years ago [6] (Table S4). e proportion of variations in each genomic feature was consistent with the above population analyses.…”
Section: Detection Of Genetic Variations In B Belcherimentioning
confidence: 56%
See 1 more Smart Citation
“…When we used the high-depth sequencing data (43.3X) to identify variations in Branchiostoma, the polymorphism rate increased to 3.69% ( Table 1, Table S1), which is still smaller than that of previously published reports (4% for B. floridae and 5.37% for B. belcheri) [2,3]. e difference in the polymorphism rate between B. floridae and B. belcheri is likely because both species have undergone a long period of independent evolution since they diverged from the most recent common ancestor approximately 100 million years ago [6] (Table S4). e proportion of variations in each genomic feature was consistent with the above population analyses.…”
Section: Detection Of Genetic Variations In B Belcherimentioning
confidence: 56%
“…Most chordates evolved into a variety of vertebrates under two rounds of whole-genome duplication (2R-WGD); however, the genome of amphioxi remained intact without any WGD events [2]. For these reasons, amphioxi are considered to be intermediate between vertebrates and invertebrates, and thus, are widely used as a model organism to study the evolution of invertebrate and the origin of vertebrates [1][2][3][4][5][6]. Previous studies have found that amphioxi are extremely genetically diverse animals with high population heterozygosity [2,3,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Divergence times for all branching points were calculated using the Maximum Likelihood method based on the GTR model. Relative times were optimized and converted to absolute divergence times based on two calibration points: the divergence times between vertebrates and cephalochordates (598-787 Ma or 603.55-697 Ma) and between cyclostomes and gnathostomes (524-706 Ma or 412.75-462.50 Ma) [21,22]. A discrete Gamma distribution was used to model evolutionary rate differences among sites and the rate variation model allowed for some sites to be evolutionarily invariable.…”
Section: Divergence Time Estimationmentioning
confidence: 99%
“…Using the Bayesian inference phylogenetic tree obtained using the different cephalochordate mitochondrial genomes and those of P. marinus, S. canicula and B. carnosus, we have estimated the divergence time between each clade using two different calibrations [21,22] (Fig 4, S1 Fig and Table 3). Thus, the estimated divergence between cephalochordates and vertebrates occurred around 700 Ma ago (787 Ma or 655 Ma depending on the calibration used, see Table 3).…”
Section: Inference Of Divergence Timementioning
confidence: 99%
“…A small sampling size of Pyrrhocoroidea likely caused incongruent phylogenetic relationships within Eutrichophora, which may have influenced the accuracy of the result and created uncertainty to true evolutionary relationships [15]. Phylogenetic analyses using concatenation of genomic-scale data have been seen as the panacea for resolving the incongruences among inferences based on a few genes or single genes [16]. However, phylogenomics may also suffer from systematic errors, due to the cumulative effects of saturation [17], among-taxa compositional (GC content) heterogeneity [18,19], or the codon-usage bias (distinct preferences for alternative synonymous codons) [20].…”
Section: Introductionmentioning
confidence: 99%